Improvising Fugitive Access: Drafting Mad Care in a Disability Arts and Culture Classroom - Esteban, Jose Miguel (Performance Matters, 2025)
How can disability arts and culture practices of access work toward a fugitive pursuit of care that rigorously dreams crip, queer, and mad worlds into be(com)ing? This critical-creative essay shares a choreographic narrative of my attempts to centre a rigour of care within the university classroom. Reflecting on my experiences as an instructor for an undergraduate course on disability arts and culture, we can enact a dramaturgical interpretation of my gestures of care by interpreting them as performances of failure. Oriented through practices of disability dramaturgy and abolitionist traditions of black study, these embodied forms of narrative and improvisational inquiry attempt to reencounter my practice of “sharing in draft”—an access practice that attempts to extend radical compassion to my/our mad movements through anxiety and depression. In doing so, we can reinterpret crip, queer, and mad gestures of failure as creative moments of fugitive improvisation.Plain Language Abstract (adapted by Kelsie Acton with Daniel Foulds)I write about teaching a disability arts and culture class in a university. I dance and write from the dancing. I feel and move my body. Those feelings and movements help me remember stories of caring for my students. I move and I think about sharing in draft. Sharing in draft is an access practice. Access practices are the actions we do to get what we need in different spaces. Sharing in draft means what I share isn’t finished and doesn’t have to be perfect. Sharing in draft helps me with what I need because of my anxiety and depression. Sharing in draft reminds me that nothing I say or do is final. I can always try again. This reminder helps me when I experience failure as a teacher. It also helps my students. Failure is something that we are taught to avoid in the university. Failure can also show us when we are not getting the support we need. This helps me to understand that sharing in draft can also be a fugitive practice. Fugitive practice means how you get away. When we recognize that a space like the university classroom is not giving us what we need, practices of fugitive access are the things we do to get away from those spaces. Practices of fugitive access are also the things that we do to create different spaces where we can get what we need by caring for ourselves and for each other.